2020
DOI: 10.5765/jkacap.200018
|View full text |Cite
|
Sign up to set email alerts
|

Visual Perception in Autism Spectrum Disorder: A Review of Neuroimaging Studies

Abstract: Although autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by social impairments, patients with ASD frequently manifest atypical sensory behaviors. Recently, atypical sensory perception in ASD has received much attention, yet little is known about its cause or neurobiology. Herein, we review the findings from neuroimaging studies related to visual perception in ASD. Specifically, we examined the neural underpinnings of visual detection, motion perception, and face processing in ASD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 142 publications
1
30
0
1
Order By: Relevance
“…Additionally, arguments of normal magnocellular function based on lack of difference in flicker contrast sensitivity between those with ASD and TD groups ( Pellicano et al, 2005 ) were based on experiments carried out at temporal frequencies (∼10 Hz) that are unlikely to challenge the temporal capability of the M neurons. In reviewing neuroimaging studies in autism, with multiple affected areas related to visual perception, Chung and Son (2020) concluded that abnormalities are not only present in early visual processing but are specifically atypical in the primary visual and extra-striate cortex including area MT.…”
Section: Update - Abnormal Dorsal Stream Development and Connectivity In Autismmentioning
confidence: 99%
“…Additionally, arguments of normal magnocellular function based on lack of difference in flicker contrast sensitivity between those with ASD and TD groups ( Pellicano et al, 2005 ) were based on experiments carried out at temporal frequencies (∼10 Hz) that are unlikely to challenge the temporal capability of the M neurons. In reviewing neuroimaging studies in autism, with multiple affected areas related to visual perception, Chung and Son (2020) concluded that abnormalities are not only present in early visual processing but are specifically atypical in the primary visual and extra-striate cortex including area MT.…”
Section: Update - Abnormal Dorsal Stream Development and Connectivity In Autismmentioning
confidence: 99%
“…In contrast to our hypothesis, participants with ASD and ADHD continued to gaze at the VR teacher more than their typically developed counterparts, even in situations where they might have been upset by auditory stimuli. This behavioral difference may be related to the influence of higher-level cognition on atypical visual perception in people with ASD [ 30 ] or the weak central integration of children with ASD [ 9 ]. Moreover, it is known that people with ADHD and ASD have difficulty switching their attention because they concentrate too much on what they are interested in.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to altered interoception in autism, several studies report perceptual variation in autism across different exteroceptive modalities [123][124][125][126][127]. For example, individuals with autism have altered visual perception, including superior performance in detail or pattern recognition tasks [128,129], and in visual search tasks [130], along with significant deficits in motion processing tasks [131,132].…”
Section: Individuals With Autism Show Atypical Perception and Motor Functionmentioning
confidence: 99%